Corporate Social Responsibility Ruangguru in media digital in times Covid-19 pandemic - Windawati Cahyaningtyas, Anindya (COMMICAST, 2022)
The global health, economic, and social impacts of the coronavirus (COVID-19) pandemic are growing day by day. Over the past few months, first China, and now the whole world has been grappling with the effects of the COVID-19 pandemic in businesses, employees, customers, communities, and each other. This paper tries to explore corporate social responsibility (CSR) in social media in times covid-19 pandemic. The research uses qualitative research methods with a case study approach. The researcher also accesses the internet to collect some data which are related to the topic. This way is chose because to find and collect data from internet and digital library is easier. Moreover, the pandemic season requires the writer to stay at home.